Adsorption of Ag (I) Ions from Aqueous Solutions Using Photocured Thiol-Ene Hydrogel - KÖK YETİMOĞLU, ECE; KAHRAMAN, MEMET VEZİR (TAYLOR & FRANCIS INC, 2013)
In this present work, we reported the adsorption and recovery studies of a P(Penta3MP4/PEG-DA/HEMA) thiol-ene based hydrogel. Real-time infrared spectroscopy technique was used to identify the photopolymerization kinetics of thiol-ene based formulations. The chemical composition and surface morphology of hydrogels were also characterized. The influence of the adsorption conditions such as pH, hydrogel formulations, contact time, initial metal ion concentration, and foreign metal ions on the metal ion binding capacity of hydrogel, were tested. Both the Langmuir and Freundlich isotherm models were applied to the method. The reusability of the hydrogels and the usability of the hydrogels for preconcentration studies were also investigated. The analytical parameters of the method were calculated and the recovery of silver ions from waste radiographic films was also applied to the hydrogels.
Keywords: adsorption; silver; thiol-ene hydrogels; waste radiographic films; CHELATING RESINS; SILVER RECOVERY; METAL-IONS; GOLD(III); REMOVAL; PLATINUM; CHITOSAN; SORPTION; AG(I); FILMS